Review on Malaysian and Thailand's perspective towards renewable energy - Shasidharan, Gomesh Nair; Misrun, Muhammad Irwanto; Yusoff, Mohd Irwan; Zambak, Muhammad Fitra; Hashim, Uda; Mariun, Norman (Trans Tech Publications, 2014)
This paper presents a review on Malaysia and Thailand’s view on renewable energy mainly in the area of solar energy. It is based on a survey conducted on random subjects in Malaysia raging from different discipline such as those from RE and non RE industries, and several learning Institution. The survey was conducted on random subject as to create a variance on their given answers. A total of 6,450 Malaysian have answered the survey which is then analyzed and compared with the views and current RE scenario in Thailand. The data analysis for Thailand is obtained from literature review. Based on the analysis, one could conclude that both Malaysia and Thailand are on the same objective which is to expand and cultivate their RE sources and has adapt an alternative method to sustain their energy development.